Civic gifts voluntarism and the making of the American nation-state - Clemens, Elisabeth Stephanie 1958- (The University of Chicago Press, 2020)
"Civic Gifts traces how practices of reciprocity and organized mass benevolence-that is, philanthropy-have contributed to the development of novel forms of national solidarity and impressive governing capacities in the United States, contributing even to a famously anti-statist political culture. Sociologist Elisabeth Clemens paints a picture of the US, whether as nation or as state, as a puzzle. How, she asks, did a sense of shared nationhood develop despite the linguistic, religious, and ethnic differences among the settlers? How did a global power emerge from an often anti-statist political culture? How did some version of this collective identity come to be articulated with organized governance? With Civic Gifts, Clemens reveals that an important piece of the answer to these questions can be found in the unexpected political uses of philanthropy and the power of gifts to mobilize communities and to create solidarity among strangers"--
Includes bibliographical references and index
Keywords: Geschichte 1780-1945; Nationalbewusstsein; Wohltätigkeitsorganisation; Solidarität; Wohltätigkeit; USA; Voluntarism / United States / History; Charity organization / United States / History; Social service / United States; Charity organization; Social service; Voluntarism; United States; History; Hochschulschrift